Isolation and characterization of encapsulated plant growth-promoting Enterobacter sp. SA10 for enhancing chili growth - Syaziana, N. Siti Anis; Othman, Nur Maizatul Idayu; Shamsuddin, Aida Soraya; Ali, Tan Kee Zuan; Mansor, Musliyana (Elsevier, 2024)
Introduction: Plant growth-promoting rhizobacteria (PGPR) can increase plant growth and encapsulation of PGPR with biochar ensures the viability and survival of PGPR. However, this approach is still underexplored. Objectives: The objectives of this study: 1) to isolate and select a potential PGPR from rice rhizosphere based on plant growth-promoting characterization, 2) encapsulate the selected PGPR strain SA-10 using biochar and sodium alginate, and 3) assess the effect of encapsulated and non-encapsulated SA-10 on chili plant growth compared to a non-inoculated SA-10 and control. Methodology: SA-10 was isolated from rice rhizosphere and characterized for plant growth promoting traits including, the nitrogen fixation, phosphate solubilization, production of siderophore, production of indole acetic acid and production of cellulose degradation enzyme. SA-10 was encapsulated in alginate beads along with biochar. A pot experiment conducted using encapsulated SA-10, non-encapsulated SA-10, and a control group to assess the effects of encapsulated SA-10 application on chili plants using complete randomized design (CRD) experimental design with four replications. Results: About 28 bacteria isolates were isolated from the rhizosphere and endospheric of rice crops to determine their effects on the growth of chili plants. The isolates were characterized with zinc, phosphate, and potassium solubilization, siderophores production, and cellulose degradation. The findings showed isolate SA-10 solubilized zinc at a rate of 41.6 %, phosphate at 50 %, and potassium at 76.9 %. It also fixed nitrogen, produced siderophores and degraded cellulose. The isolate also produced the highest IAA at 4.007 mg/L. Isolate SA-10 was then encapsulated in a mixture of biochar and sodium alginate. The results showed that plants treated with encapsulated SA-10 had significantly higher leaf area (3.68 cm2), leaf diameter (6.55 cm), and dry weight (0.39 g) compared to those treated with non-encapsulated and the control treatment. Through 16S rRNA gene sequencing, it was identified that SA-10 belongs to the Enterobacter genus, closely resembling Enterobacter chuandaensis. Conclusion: The findings suggest that Enterobacter sp. SA-10 enhances plant growth, and the use of encapsulated SA-10 with biochar contributes to the growth of chili plants. The encapsulated Enterobacter sp. SA-10 has a promising potential in enhancing crop yield production and promoting sustainable agriculture.